2017
DOI: 10.9775/kvfd.2017.17480
|View full text |Cite
|
Sign up to set email alerts
|

Süt ve Peynirden İzole Edilen Bacillus cereus’un Prevalansı, Enterokoksin Üretimi ve Antibiyotik Direnci

Abstract: Bacillus cereus is a type of bacteria that can cause severe food poisoning. The aim of this study was to determine the incidence of B. cereus in various full-fat milk and cheese samples and to assess the HBL (haemolysin BL) and NHE (nonhaemolytic enterotoxin) production and the resistance to several antimicrobial agents of the isolates. A total of 259 samples of full-fat milk (raw, pasteurized and UHT) and cheese obtained from different retail markets in Bursa province between July and December 2013 were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
(16 reference statements)
5
5
0
1
Order By: Relevance
“…The isolates obtained from the analyzed Taleggio production plant showed a constant ability to produce PC-PLC, proteases, and hemolysins, whereas only most of them were able produce HBL (66.7%). These results agree with previous studies showing a very high rate of PC-PLC, protease, and hemolysin activity [4,[31][32][33], and a variable rate of HBL production (ranging from 20 to 90%) by B. cereus isolates [21,34,35].…”
Section: Virulence Potential Of B Cereus Isolatessupporting
confidence: 93%
See 1 more Smart Citation
“…The isolates obtained from the analyzed Taleggio production plant showed a constant ability to produce PC-PLC, proteases, and hemolysins, whereas only most of them were able produce HBL (66.7%). These results agree with previous studies showing a very high rate of PC-PLC, protease, and hemolysin activity [4,[31][32][33], and a variable rate of HBL production (ranging from 20 to 90%) by B. cereus isolates [21,34,35].…”
Section: Virulence Potential Of B Cereus Isolatessupporting
confidence: 93%
“…Considering cheese, several studies confirm the high prevalence of nhe genes in B. cereus isolates [21,31,32,[35][36][37][38]. In this study, we found that all the strain clusters harbored nheA, and some also nheB (83.3%) and nheC (66.7%), indicating that 66.7% of the strains are potentially able to secrete active NHE.…”
Section: Virulence Potential Of B Cereus Isolatessupporting
confidence: 72%
“…Various studies reported different rates of B. cereus s.l. contamination: in dried food samples of different pulses and cereals 56% [ 34 ]; in pasteurized milk 27% to 47% [ 30 , 35 , 36 , 37 ]; in milk and dairy products 14% to 70% [ 38 , 39 , 40 , 41 ]; in ice cream 30% to 63% [ 6 , 31 , 38 , 41 ]. Our study investigated the presence of the B. cereus group in ice creams, which was estimated to be 65% (33/51); a similar prevalence (62.7%) was described in Messelhausser U. et al, 2010 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were almost like those of Zhao et al (2020), who concluded that 94.4 % of B. cereus harboured nhe gene, while cytK gene was present in a higher percent (75.9 %) than our findings. Yibar et al (2017) recorded that 42.3 % of B. cereus isolates from the examined different cheeses types harboured nhe gene. There was a significant difference (p<0.05) between nhe and ces genes in all investigated samples except in flavoured drinking yogurt, which indicates a high association of these genes with these products.…”
Section: Discussionmentioning
confidence: 99%